Chemical composition, antioxidant, and anti-inflammatory activities of essential oils from Cymbopogon citratus (DC.) Stapf and Chrysopogon zizanioides (L.) Roberty cultivated in Kisangani, Northeastern Region of the Democratic Republic of the Congo - NDEZU ANGIRIO, Rachel; Mbinze, Jérémie Kindenge; K. Tafokeu Taguimjeu , Pierre-Leonel; Mouithys-Mickalad, Ange; Gregoire, Maxime; Thierry, Franck; Mankulu Kakumba, Jocelyn; Ive Kitenge, Dadit; Genva, Manon; Kadima Ntokamunda, Justin; Fauconnier, Marie-Laure; MARINI DJANG’EING’A, Roland (Orapuh Journal, 2025)
Introduction Essential oils are valuable natural products known for their bioactive properties. Cymbopogon citratus (lemongrass) and Chrysopogon zizanioides (vetiver) are aromatic plants cultivated in Kisangani, whose chemical composition and biological activities warrant investigation. Purpose This experimental study aimed to determine the chemical composition and to evaluate the in vitro antioxidant and anti-inflammatory properties of essential oils extracted from Cymbopogon citratus (DC.) Stapf and Chrysopogon zizanioides (L.) Roberty cultivated in Kisangani. Methods Leaves of lemongrass and roots of vetiver were collected from the Mavaolo concession and hydro-distilled to obtain essential oils (EOs). The extraction yields were 0.11 ± 0.01% for lemongrass and 1.40 ± 0.67% for vetiver, with densities of 0.88 µg/mL and 1.05 µg/mL, respectively. Gas Chromatography–Mass Spectrometry (GC–MS) analysis revealed 17 and 24 peaks in the two species, of which 100% and 82.32% were identified, respectively. Results C. citratus oil consisted mainly of oxygenated monoterpenes (69.93%), primarily citral (36.64%) and nerol aldehyde (28.85%), while C. zizanioides oil contained predominantly oxygenated sesquiterpenes (87.67%), including khusimol (28.52%) and vetivenic acid (14.01%). Lemongrass essential oil exhibited strong antioxidant and anti-inflammatory activities, whereas vetiver oil showed weak antioxidant but strong anti-inflammatory properties compared with α-tocopherol used as a reference. Conclusion The findings indicate that C. citratus and C. zizanioides cultivated in Kisangani contain bioactive constituents of commercial potential. It is recommended that further cultivation studies be conducted to optimise essential oil yield.